Does outreach matter? Examining the relationship between outreach efforts and recycling amounts - Gahan-Hunter, Tarna (My University, 2009)
This research project seeks to determine the extent to which outreach and enforcement activities impact the per capita recycling tonnage of municipalities in Wisconsin. The Wisconsin Department of Natural Resources (DNR) requires that Responsible Units undertake public outreach and education efforts to increase the effectiveness of the recycling program. In addition to outreach programs, Responsible Units use enforcement activities to implement mandatory recycling. In 2002, a report on recycling in Wisconsin found that outreach had not improved in the past ten years. Research suggests that outreach programs may increase recycling amounts. Building upon this research, this project uses data collected from the DNR and the 2000 Census to determine if a relationship exists between the type of outreach and enforcement activities used and the effectiveness of the recycling program. This study is important to both measure the success of the current outreach programs, and to provide research on what type of outreach programs are the most effective for future implementation.
A field project submitted in partial fulfillment of the requirements for the degree of master of Public Administration.
Keywords: recycling, public administration evaluation, bureaucracy evaluation, outreach, ourtrach effectiveness, refuse and refuse disposal